DEVELOPMENT OF LITERARY RESEARCH METHODS ADVANCING THEORETICAL AND PRACTICAL INSIGHTS - Siti Salwa Yusyifa (As-Sulthan Journal of Education, 2025)
This research examines the development of library research methods which aim to identify, analyze and synthesize information from various written sources, such as scientific journals, books and related documents. The research approach involves exploration of the literature through academic databases such as Google Scholar and Scopus, as well as thematic, chronological and methodological analysis to identify research patterns, trends and gaps. This method offers high flexibility in various fields of knowledge, both social, technological and scientific. Data analysis was carried out using a thematic approach to identify main themes, a chronological approach to understand research development, and a methodological approach to compare methods used in previous studies. As a result, this research succeeded in identifying patterns, trends and research gaps that can be used as a basis for further research. This study also illustrates the application of literature methods to the analysis of the impact of artificial intelligence (AI) technology in higher education, demonstrating the benefits of AI in increasing the personalization of learning as well as teaching efficiency, despite the challenges of technology adoption.